Mortality among single fathers as compared with single mothers and partnered fathers: a cohort study - Chiu, Maria; Rahman, Farah; Vigod, Simone; Lau, Cindy; Cairney, John; Kurdyak, Paul (International Journal of Population Data Science, 2018)
Introduction Single-parent families are becoming increasingly common around the world with a particularly steep rise in households headed by single fathers. Research suggests that single parenthood is associated with adverse outcomes, however, little is known about the health profile or risk of death of single fathers compared to other parents. Objectives and Approach We aimed to examine mortality risk in single fathers compared to single mothers and partnered parents, which is the first head-to-head comparison of single and partnered parent groups. Our population consisted of 871 single fathers, 4590 single mothers, 16,341 partnered fathers and 18,688 partnered mothers. We combined cross-sectional samples derived from the Ontario component of Statistics Canada’s Canadian Community Health Survey (2001 to 2012) linked to health administrative databases to identify medical conditions, health service use, all-cause mortality and cause of death. We investigated differences in mortality using Cox proportional hazards models adjusted for socio-demographic characteristics, lifestyle and clinical factors. Results Each family group was followed up for a median of 11.10 years (IQR 7.36–13.54). Single fathers had a poor risk profile, particularly among lifestyle factors, such as low fruit and vegetable consumption and alcohol consumption. The mortality rate was three-fold higher for single fathers compared to single mothers and partnered fathers (5.81, 1.74 and 1.94, respectively). Even after adjustment, single fathers had a significantly higher risk of death compared to both single mothers (hazard ratio (HR): 2.49 (95% CI: 1.20 – 5.15, p=0.01)) and partnered fathers (HR: 2.06 (95% CI: 1.11 – 3.83, p=0.02). Small sample sizes precluded us from identifying the leading cause of death for single fathers. Conclusion/Implications We found that single fathers had the least favorable risk factor profile and greatest risk of mortality, which may be mitigated by physician intervention. Our study highlights that through cross-sectoral data linkages we can further advance our knowledge of social factors and their profound effects on health.